Shifting Professional Identity Among Indonesian Medical Practitioners During the COVID-19 Pandemic. (April 2023) - Adisaputri, Gianisa; Ungar, Michael
The COVID-19 pandemic has had a significant impact on medical practitioners' professional identities due to its novelty and intensity. Using constructivist grounded theory, we investigated how the COVID-19 pandemic shifted individuals' identities as medical practitioners in Indonesia, where the pandemic caused high death rates among healthcare workers, particularly medical practitioners. By interviewing 24 medical practitioners and analyzing relevant documents and reports, we developed a grounded theory of professional identity shifts. We found two patterns: (1) identity growth, in which the medical practitioners thrive and claimed stronger professional identities, and (2) psychological and moral distress leading to attrition, facilitated adaptation, or professional identity collapse. We also found several primary protective factors including religious beliefs, good leadership, team cohesion, healthy work boundaries, connection to significant others, and public acknowledgment. Without adequate protective factors, medical practitioners experienced difficulties redefining their professional identities. To cope with the situation, they focused on different identities, took some time off, or sought mental health support, resulting in facilitated adaptation. Others resorted to attrition or experienced professional identity collapse. Our findings suggest that medical practitioners' experience of professional identity shifts can be improved by providing medical practitioners with opportunities for knowledge updates, better organizational leadership and work boundaries, strategies to enhance team cohesion, and other improvements to medical systems.